Increased levels of synaptic proteins involved in synaptic plasticity after chronic intraocular pressure elevation and modulation by brain-derived neurotrophic factor in a glaucoma animal model - Hae-Young Lopilly Park; Si Won Kim; Jie Hyun Kim; Chan Kee Park (The Company of Biologists, 2019)
The dendrites of retinal ganglion cells (RGCs) synapse with the axon terminals of bipolar cells in the inner plexiform layer (IPL). Changes in the RGC dendrites and synapses between the bipolar cells in the inner retinal layer may critically alter the function of RGCs in glaucoma. The present study attempted to discover changes in the synapse using brain-derived neurotrophic factor (BDNF) after glaucoma induction by chronic intraocular pressure elevation in a rat model. Immunohistochemical staining revealed that the BDNF-injected group had a significant increase in the level of synaptophysin, which is a presynaptic vesicle protein, in the innermost IPL compared with the phosphate-buffered saline (PBS)-injected group. SMI-32, which is a marker of RGCs, was colocalized with synaptophysin in RGC dendrites, and this colocalization significantly increased in the BDNF-injected group. After the induction of glaucoma, the BDNF-injected group exhibited increases in the total number of ribbon synapses, as seen using electron microscopy. Expression of calcium/calmodulin-dependent protein kinase II (CaMKII), cAMP-response element binding protein (CREB) and F-actin, which are key molecules involved in synaptic changes were upregulated after BDNF injection. These initial findings show the capability of BDNF to induce beneficial synaptic changes in glaucoma.